A toponímia da região Central Mineira - Patricia de Cassia Gomes Pimentel (2015)
In this study, we will investigate e describe the toponimic lexicon of the Mineira Central Region, based on names of African and indigenous origin, which give names to physical and human accidents in that part of the Central Mineira land.Toponymy studies are of fundamental importance for the knowledge of cultural and historical aspects of a certain community because they rescue the society´s intention in the process of naming places in the environment, even when there is a lack of semantics due to the passage of time. Being part of the Minas Gerais state toponymic ATLAS ATEMIG, which our corpus came from, this study followed the references, theoretical and methodological, proposed by Dauzat (1926) and Dick (1990, 1990a and 1990b) to develop the investigation of onomastics proposed by this research. We selected 4.069 toponyms that refer to the Mineira Central Region, from the 85.391 found in the synchronic dada bank of ATEMIG. From those 4.069 toponyms, we identified 768 from indigenous origin and 98 from African origin. For the linguistics analyses of these dada, we used different dictionaries, being them, part of the etymology and the morphology fields in Portuguese. Besides that we also checked specific vocabularies that gather words from indigenous and African origins, such as Castro (2001) and Sampaio (1987). Talking about the origin of toponyms, we could verify the predominance of the Banto basis for the African terms and the Tupy basis for the indigenous terms. There is also a quite high amount of hybridisms African/Portuguese and indigenous/Portuguese. The analyses of taxonomic toponyms showed that, between the toponimys of African origin, the major occurrence found were for the taxonomys of anthropological and cultural nature; on the other hand, between the toponyms of indigenous origin, the major occurrences verified were between the taxonomys of physical nature. Because of that, we could verify as well that the toponimic motivation more recurrent between the toponimys of African origin is related to human social activities, professional activities and of work places of a certain community, the sociotoponyms; while, for the toponyms of indigenous origin, the most frequent motivation is related to the environment, more specifically plants and vegetation, the phytotoponyms.